Variasi Kandungan Minyak dan Asam Lemak Rantai Medium Kelapa Lokal pada Elevasi yang Berbeda - ELSJE T. TENDA (Pusat Penelitian dan Pengembangan Perkebunan, 2009)
Variation of Oil and Medium Fatty Acid Chain of Local Coconut from Different ElevationThe research was conducted from March to December 2007 by using nine cultivars of local tall from farmers plantation in North Minahasa, South Minahasa and Bolaang Mongondow regions of North Sulawesi. The sample from each regions was taken out from three different elevation. Each cultivars was selected 15 palms and each palm was taken two mature nuts. VCO processing was done using stage heating and natural fermentation. Fatty acid content was analized at BBIA-Bogor and FTP – UGM laboratories. Beside of that, has been done oil content analyzes of kernel. The result showed that elevation did not influence to oil content and médium chain fatty acid (MCFA). MCFA of VCO from stage heating process almost the same with natural fermentation process.